In Vivo Genotoxicity Testing Strategies: Report of the International Workshop on Genotoxicity Testing (IWGT) - Beevers, C.; Uno, Y.; Meurer, K.; Hamada, S.; Hashimoto, K.; Le Hegarat, L.; Kirkland, D.; LeBaron, M. J.; Le Curieux, F.; Martus, H. J.; Masumura, K.; Ohyama, W.; et al. (Spanish Journal of Environmental Mutagenesis and Genomics, 2023)
The in vivo testing strategies working group (WG) at the International workshop on genotoxicity testing (IWGT) discussed topics related to in vivo testing. Key conclusions from the group will be discussed. The majority of the WG group agreed that it is unacceptable to reject the conclusions of a negative in vivo erythrocyte MN study solely on the basis of test substance concentrations in blood or plasma falling below the concentration that induced positive results in vitro. Consensus on the evidence required to demonstrate systemic exposure was not reached. The WG members agreed that the liver MN test is sufficiently validated to develop this test into an OECD Test Guideline, however, the impact of age at the time of dosing warrants further study. The WG agreed that Ki-67 is a reliable marker for mitotic activity, however, the evaluation of longer-lived cell proliferation markers would be valuable. The WG agreed that comparison of comet study results to historical control data (HCD) for determination of biological relevance should not be performed used unless the laboratory can demonstrate stability of their HCD, and that animal (but not study) factors are the predominant source of variance in the HCD. The WG agreed that methodological differences could influence the risk of both false positive and false negative results.